Mengenalkan Teknologi 3D Printing untuk Pembuatan Suvenir Miniatur Arca dan Candi Borobudur - Ikhwan Taufik; M. Fendy Kussuma Hadi Sufyan; Jalu Aji Prakoso; Nandang Riski Setiawan; Reyvan Alfian Nurkhamid (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
The main issue faced by the partner is the production of miniature statue and temple souvenirs made from natural stone through carving or engraving processes. The extensive and long-term use of natural stone will damage the ecosystem, especially rocks. Moreover, natural stone is formed through a very long geological process. 3D printing to create miniature statue and temple souvenirs is an alternative solution to increase the variety of souvenir products in Kalirejo Tourism Village while preserving the ecosystem, particularly rock diversity. This is because 3D printing technology uses biodegradable materials. However, the marketing of souvenirs, as a key support for the tourism sector, still needs to be improved. Through the marketing and sale of miniature statue and temple souvenirs made using 3D printing technology, the target of increasing the partner’s sales turnover by up to 10 percent from previous figures can be achieved. One of the key factors supporting the success of this activity is the strong cooperation and active participation of the partner during its implementation. The Kalirejo Village Government also provided full support to ensure the smooth execution of the program.